Kyberhuoltovarmuus kokonaisturvallisuuden näkökulmasta - Puuperä, Sami (2024)
The continuous evolution of the security environment underscores the im-portance of proactive preparedness and resilience in maintaining societal cri-sis resistance. Digital environments are particularly crucial for the critical functions of society, offering new opportunities but also increasing cyber threats that can endanger vital societal activities through cyber-attacks. This is especially true in a country like Finland, where the digital infrastructure is extensively integrated into the core functions of society, highlighting the stra-tegic significance of cybersecurity. From the perspectives of cybersecurity and resilience, international co-operation, legislative development, and effective national strategies and their implementation are key elements in managing cyber threats. In addition to national actions, Finland's active participation in international cybersecurity initiatives and agreements supports the effective implementation of the coun-try's cybersecurity strategy. This cooperation allows for the sharing of infor-mation, resources, and best practices, strengthening global cyber resilience. Finland is recognized as a leader in cybersecurity, continuously striving to maintain a high level of security and improve resilience to quickly respond to the evolving cyber environment. This study demonstrates how actions tak-en in the cyber dimension of resilience are an inseparable part of national and international security, emphasizing the strategic importance of cyber resili-ence. The research report provides an overview of the current state of cyber re-silience, its challenges, and future development directions in Finland and in-ternationally. It addresses in detail the critical issues of cyber resilience, such as the growth in technological dependency, the complexity of cyber-attacks, and the vulnerability of infrastructure. Additionally, the report explores the possibilities and challenges of developing cyber resilience and how Finland can continue its role among the leading nations in cybersecurity. The report aims to provide recommendations to further enhance Finland's cyber resili-ence and Comprehensive security.